Estimating the benefit of esketamine nasal spray versus real-world treatment on patient-reported functional remission: results from the ICEBERG study - Oliveira-Maia, Albino J.; Rive, Benoît; Godinov, Yordan; Mulhern-Haughey, Siobhán (Frontiers in Psychiatry, 2024)
Treatment resistant depression (TRD) affects approximately 10-30% of patients with major depressive disorder, and most patients with TRD do not respond to real-world treatments (RWT). Treatment with esketamine nasal spray (NS) plus a selective serotonin or serotonin norepinephrine reuptake inhibitor (SSRI/SNRI) has significant long-term clinical benefit over RWT in patients with TRD. However, the impact on patient-reported function remains to be determined.The ICEBERG analysis was an indirect treatment comparison performed using data from two studies of patients with TRD: SUSTAIN-2 (esketamine NS; NCT02497287) and the European Observational TRD Cohort (EOTC; RWT; NCT03373253; clinicaltrials.gov). Here, patient-reported functional remission, assessed using the Sheehan Disability Scale (SDS), was defined as SDS ≤6 at Month 6. Analyses were conducted using propensity score re-weighting and multivariable models based on 18 covariates.At Month 6, the probability of functional remission in esketamine NS-treated patients from SUSTAIN-2 (n=512) was 25.6% (95% confidence interval [CI] 21.8-29.4), while the adjusted probability for RWT patients from the EOTC (n=184) was 11.5% (95% CI 6.9-16.1; relative risk: 2.226 [95% CI 1.451-3.416]; p=0.0003). In the total combined population (n=696), patients who did not achieve clinical response or remission had a low probability of achieving functional remission (5.84% and 8.76%, respectively). However, for patients who did achieve clinical response or remission, the probability of achieving functional remission was greater (43.38% and 54.15%, respectively), although many still did not achieve this status.For patients with TRD, esketamine NS had a significant functional benefit versus RWT after 6 months of treatment. Irrespective of treatment, achievement of clinical response or remission was insufficient to attain functional remission. Nevertheless, clinical remission increased the likelihood of achieving functional remission, further supporting an important role for clinical remission in for the path towards functional recovery.